Enhancing fourth graders’ ability to interpret graphical representations through the use of microcomputer-based labs implemented within an inquiry-based activity sequence - Nicolaou, Christiana T.; Nicolaidou, Iolie; Zacharia, Zacharias C.; Constantinou, Constantinos P. (My University, 2007)
This article reports on a research effort that investigated whether the use of Microcomputer-Based Labs (MBLs), implemented within an inquiry-based activity sequence on phase transformations (melting and freezing), contributes to the development of fourth grade (9-10 year-old) students' conceptual understanding and ability to construct and interprete graphs. The participants of the study were 65 fourth graders (organized into an experimental and two control groups). The experimental treatment involved the use of an inquiry-oriented activity sequence along with the use of MBLs. The control treatment for the first control group involved the use of the inquiry-based curriculum without the support of MBLs, whereas, the control treatment for the second control group involved the use of traditional laboratory methods. Data was collected through the use of a conceptual test administered to students both before and after the study. The results of the study revealed a statistically significant difference between the experimental group and both control groups in students' ability to construct and interprete graphs, and their understanding of phase transformations.
Keywords: Microcomputer-Based Labs; Fourth Graders; Inquiry-Based Activity Sequence; Assessment; Curriculum; Educational Technology; Instructional Materials